PLGA and PLA particles as vaccine delivery systems for Atlantic salmon : a study on formulation and use with an emphasis on immune responses - Fredriksen, Børge Nilsen (University of Tromsø, 2012)
Papers 1-4 of this thesis are not available in Munin: 1. B.N. Fredriksen, K. Sævareid, L. McAuley, M.E. Lane, J. Bøgwald and R.A. Dalmo.: 'Early immune responses in Atlantic salmon (Salmo salar L) after immunization with PLGA nanoparticles loaded with a model antigen and β-glucan', Vaccine (2011) 29(46):8338-8349. Available at http://dx.doi.org/10.1016/j.vaccine.2011.08.087 2. B.N. Fredriksen and J. Grip.: 'PLGA/PLA micro- and nanoparticle formulations serve as antigen depots and induce elevated humoral responses after immunization of Atlantic salmon (Salmo salar L)', Vaccine (2012) 30(3):656-667. Available at http://dx.doi.org/10.1016/j.vaccine.2011.10.105 3. H.M. Munang‟andu, B. N. Fredriksen, S. Mutoloki, B. Brudeseth, T.Y. Kuo, I. S. Marjara, R.A. Dalmo and Ø. Evensen.: 'Comparison of vaccine efficacy for different antigen delivery systems for infectious pancreatic necrosis virus vaccines in Atlantic salmon (Salmo salar L)' (submitted manuscript). 4. B.N. Fredriksen, L.B. Hølvold, J.Bøgwald and R.A. Dalmo.: 'Optimization of formulation variables to increase antigen entrapment in PLGA particles' (submitted manuscript). Vaccines are regarded as the safest and most cost-effective strategy to prevent infectious diseases. For some diseases, vaccine improvements are required as protection levels are still inadequate. The key to solving this challenge might lie in the development of more efficacious vaccine delivery systems and adjuvants. Poly (lactide-co-glycolide) (PLGA) is a biodegradable polymer which has an extensive safety record in biological systems and possesses immunological adjuvant properties as injectable particles. In the present work, micro- and nanoparticles of PLGA and PLA were explored as a vaccine delivery system in Atlantic salmon (Salmo salar). The overall objectives were to investigate their adjuvant abilities in provoking innate and adaptive immune responses, forming antigen depots and inducing protective immunity in a challenge test with infectious pancreatic necrosis virus (IPNV). ...